Pengembangan Perangkat Pembelajaran Problem Based Learning dengan Konsep Assesment for Learning Berbantuan Articulate Storyline 3 - Nurisma Siti Yuniar; Elvin Yusliana Ekawati; Sukarmin Sukarmin (Jurnal Materi dan Pembelajaran Fisika, 2023)
The objectives of this development research were to: (1) develop problem-based learning tools with the concept of assessment for learning assisted by articulate storyline 3 on temperature and heat material; (2) analyzing the product evaluation criteria for problem-based learning devices with the concept of assessment for learning assisted by articulate storyline 3 on temperature and heat material. This study uses the Research & Development (R&D) model with 3 stages, namely analysis, design, and development. The data needed are qualitative data and quantitative data. Data analysis was obtained from the assessment of two lecturers, two teachers, five colleagues, and readability by class XI students, totaling 32 students. The research school used was SMA N 5 Surakarta. Data analysis was guided by Azwar's assessment criteria. As for the knowledge assessment instrument, analysis was carried out using Anbuso and IBM SPPS Statistics. Data collection was carried out by distributing questionnaires, tests and interviews. The conclusions obtained based on research are: (1) The development of learning tools is prepared using a problem based learning model by inserting the concept of assessment for learning, namely the Learning Implementation Plan (RPP), Student Worksheets and knowledge assessment instruments. The device is prepared by adjusting the learning media assisted by articulate storyline 3. The learning media is divided into three parts, namely temperature media and the concept of heat, expansion media, and heat transfer media. (2) The results of the data analysis that has been carried out show that the lesson plans and worksheets have very good criteria and the knowledge assessment instruments are accepted with high reliability.